Conditional Harmony: The Relations between Mining Company and Local People - Gilang Mahadika (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2021)
Mining corporation plays a role as surrogate state since it takes after the state in its development agenda. One of the biggest coal mining companies in Indonesia, PT. KPC (Kaltim Prima Coal), has carried out several activities other than mining ones. The activities are manifested in CSR (Corporate Social Responsibility) programs. An obligation to recover post-mining area by KPC is already implemented in a program called PESAT (Integrated Cattle Farm) which is one of the CSR programs. The farm in the recovered post-mining area is developed as a social program for people living around the mining area. My research was carried out with qualitative approach. Participatory observation and interviews with people in the village of Swarga Bara, Kutai Timur, East Kalimantan, were used in collecting data. The result shows that the people living around the KPC is an active agent in responding the corporate lives. The local people, in fact, depend on the KPC’s social programs since the programs are in favor of local development and welfare. Nevertheless, the local people respond negatively toward programs which do not meet their needs